Dominica : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper discusses the optimal management of Citizenship-by-Investment (CBI) program revenues in Dominica. Dominica's CBI inflows have reached near 10 percent of GDP, increasing the country's reliance on these revenues. It is argued that given their volatile and unpredictable nature, CBI revenues should be used prudently. Their use should be mindful of the chances of a sudden stop in these flows. It is therefore essential to prioritize investment, debt reduction, and saving in lieu of current expenditure, which is typically more difficult to reverse. Simulation analysis based on fiscal multipliers indicate that such combination of policies would boost GDP and help reach the regional debt target of 60 percent of GDP by 2030 as committed by the government.